Anti-pattern Free Code-first Web Services for State-of-the-art Java WSDL Generation Tools - Ordiales Coscia, José Luis (2013)
Service-Oriented Computing (SOC) promotes structuring applications via coarse-grained, remote components called services. To materialise SOC, web services is the most common choice. A web service comprises an implementation and a description using the Web Services Description Language (WSDL). Web services are often built by first implementing their behaviour and then generating its WSDL document via automatic tools. However, bad design practices already present in a service implementation may end up affecting the quality of its WSDL document. For web services to be reusable, good WSDL designs are crucial. Previously, Mateos et al. show that there is a high correlation between Object-Oriented (OO) metrics from service implementations and the occurrences of 'anti-patterns' in WSDL documents. In this follow-up paper, these results are extended to all the existing WSDL generation tools. A detailed analysis of the impact of OO metric-driven code refactorings on the quality of WSDL documents is also reported.